PENGARUH WORK MOTIVATION TERHADAP JOB SATISFACTION MELALUI ORGANIZATIONAL CULTURE (Studi Literatur) - Moch. Geri William (Yos Soedarso Economic Journal (YEJ), 2020)
This literature study aims to determine the effect of work motivation on job satisfaction through organizational culture. The literature study is based on 20 international journals and data is collected using search engine methods. The results show that the work motivation system has a positive effect on job satisfaction through organizational culture and organizational culture plays an important role in supporting this influence.Keywords: Organizational Culture; Work Motivation; Job Satisfaction